“Eu não gostava nem odiava porque eu não entendia nada!”: relações com a escola, o aprender e os conhecimentos escolares no ensino médio - Martinez, Lucas da Silva (2018)
This dissertation is part of the Research Line LP2 – Práticas Escolares e Políticas Públicas of the Programa de Pós-Graduação em Educação of the Universidade Federal de Santa Maria (UFSM) and has the theme Youth, High School and relationships with the school, learning and school knowledge. The objective of the research is to understand the relations with the school, the learning and the school knowledge constructed in High School by some young students of degrees of UFSM based on their narratives, considering the influence of these relations in their mobilization or demobilization for the studies. The research is based on a qualitative approach based on Gatti (2002), Ghedin and Franco (2011) and Melucci (2005) and uses the biographical-narrative method from Bolivar, Domingo and Fernández (2001) and Clandinin and Connelly (2015). The data production was based on narrative interviews with six undergraduate students from UFSM, from the courses of Physics, Chemistry, Theater, Physical Education, Social Sciences and Pedagogy, based on Jochelovitch and Bauer (2002), Muylaert et al. , (2014) and Bolívar, Domingo and Fernández (2001). The analysis of the data was based on the Discursive Textual Analysis, based on Moraes (2003) through the disassembly of texts, categorization and abstraction of the new emergent, recorded as a metatext in chapter 6 of the dissertation. The theoretical foundations that support this work are concentrated in three main themes: High School, based on authors such as Krawczyk (2011), Kuenzer (2005), Sposito e Souza (2014), Tomazetti et al., (2014), Zibas (2005) among others; Youth, from authors such as Biscoli (2013), Dayrell (2003), Kehl (2004), Margulis and Urresti (2008), Melucci (2004), Pais (2006) Sposito (1997), among others, Relationship with knowledge from Bourdieu (2007), Charlot (2000, 2013, 2016), Freire (1983, 2011), Masschelein and Simons (2014, 2015), Perrenoud (1995) and others. The results show a set of complex relationships that surround different aspects such as: a) liking the school; b) meanings of knowledge and school activity, such as those related to the use of technology, the importance of curiosity and questioning, the teacher's explanation, the challenges in the activities and the senses linked to the future, when problematizing the “Novo Ensino Médio”; c) different experiences promoted in the school, especially those that relate the body; d) The relationship with teachers, through friendship, of the dialogical posture in the classroom, but also, the negative impacts of authoritarianism, licentiousness and lack of teacher training; e) The relationship with colleagues, which is marked by both socialization and negative aspects, which is the case of Bullying; and f) relationships established with the family and in other aspects, regarding the formation and identity of the young person.